The Effects of Lean and Agile Management on Work Effectiveness and Efficiency: A Case Study of Administration Public Service Department in Sumedang, Indonesia - Arip Rahman Sudrajat (Universitas Sultan Ageng Tirtayasa, 2021)
The purpose of this study is to determine whether there is an effect between lean and agile management towards work effectiveness and work efficiency and their impact on service performance. This study uses a quantitative method with the number of respondents as many as 50 employees. To obtain the data, the structural approach to Equation Model (SEM) is used. The results show that lean and agile management had a significant positive effect on service performance, work effectiveness, and work efficiency at the Sumedang Civil Service Department.